Evolución tectónica y metalogénesis del Perú - Acosta Ale, Jorge Gilberto (2017)
[EN] Improving the chances of success of mineral exploration requires to interconnect metallogenetic analyses with the geological evolution of western Peru that can be reconstructed from current knowledge and ongoing investigations. This communication presents a preliminary stage in this research.